Defiant publics : the unprecedented reach of the global citizen - Drache, Daniel, 1941-; Froese, Marc D. (Cambridge, UK ; Malden, MA : Polity, 2008)
"Social activism and dissent have become global phenomena for our times. This newly potent political force has defeated governments in India and Spain, and has brought down the EU draft constitution. Disaffected by the triumph of markets, public goods, public interest, and public spaces are regaining political ground. Daniel Drache argues that, feeding off distrust and suspicion of governments, and assisted by the new cultural flows of people, ideas, and information, this is a political phenomenon without historical precedent. No one owns the new public, elites remain baffled by its power and impact. No one can contain its innovative, inclusive, and rapidly evolving organizational style or determine when the current cycle of dissent will peak."--BOOK JACKET.
Includes bibliographical references (p. [184]-186) and index.
Keywords: Dissenters; Political activists